Effect of offset distances for rod-airfoil interaction noise - Jiang, Shujie; Li, Lanqing; Guo, Xiaokun; Zhao, Weiming; Zhang, Rongping; Wang, Chao (Frontiers in Physics, 2023)
The noise generated by the interaction between the wake of rods and airfoils is a universal phenomenon in the engineering field. The noise generation mechanism is mainly caused by the violent changes of the pulsating pressure on the airfoil surface, impacted by different vortex scales in the wake of rods. During this process, the energy is radiated outward by sound waves. To capture wakes and the sound generated by the interaction of rod-airfoil with relatively small computing resources is a challenge. In this paper, the sound pressure generated by the rod-airfoil interaction is calculated by solving the Reynolds average N-S equation and non-linear acoustic equations. This numerical method is verified by a rod-airfoil interaction benchmark. This paper focuses on the influence of offset distances between rods and airfoils. The results show that the peak of far-field sound decreases from 89dB to 80.6dB as the offset distance from the airfoil to the center of the cylinder increases (the maximum deviation is three times the cylinder diameter). The frequency of peak sound pressure also shifts.